Management of unilocular or multilocular cysts more than 5 centimeters in postmenopausal women. (August 2016) - Guraslan, Hakan; Dogan, Keziban
Abstract: Objective: To evaluate the malignancy potential of large unilocular and multilocular ovarian cysts in postmenopausal women and to discuss their appropriate management. Study design: This retrospective study included 204 postmenopausal patients who underwent surgery for simple adnexal cysts or cysts with isolated septal structures at the Gynecology and Obstetrics Clinic of Bakirkoy Dr Sadi Konuk Training and Research Hospital. Data obtained from patient and computer records included patient age, follow-up period, ultrasonography reports, surgery information, histopathological evaluation results, and cancer antigen-125 (CA-125) levels at diagnosis and during follow-up. The Kruskal–Wallis test was used to compare three or more groups. The Chi-square test or Fisher's exact test was used to compare qualitative parameters, while relationships between parameters were analyzed by using Spearman's correlation analysis. Results: A total of 236 cysts were identified in 204 postmenopausal women who underwent surgery. The cysts were categorized as having unilocular cyst morphology or complex structures without morphological abnormalities other than septa in 182 (77.1%) and 54 cases (22.9%), respectively. The mean cyst diameter was 6.6 ± 3.1 cm (range, 2.7–30 cm) with diameters ≥5 cm in 176 cysts (75%). The median cyst volume was 88.5 cm 3 (range, 10–2636; interquartile range: 81) and the mean morphology index was 1.2 (range, 1–6), with 16 cysts (6.8%) ≥5. No malignancy or borderline histology was observed in any patient. Conclusions: Among postmenopausal women, cysts that are unilocular or contain isolated septa, have a low-risk of malignancy even when they are larger than 5 cm. Rather than undergoing emergency surgery, these patients may be followed up conservatively with intermittent transvaginal ultrasonography.